(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Media have the power to shape, influence and construct public opinion. Media proves to be instrumental in environmental sensitisation, and endorsing environment-friendly practices. In this era, covering environmental issues may be considered as one of the primary functions of the media. Media have function to teach the art of effective and environment-friendly agriculture practices to the farmers. It has a role to disseminate scientific knowledge in an easily and understandable form. The use of picture-supported communication for the improvement of agricultural extension may result in icing on the cake. In this regard, the study aimed to gauge the coverage garnered by agriculture in leading Indian English dailies. It also aimed to analyse the trend in covering agriculture by Indian English dailies at various points in time. Content analysis of the newspapers reveal that agriculture in totality has been allocated a minuscule space of 0.20 per cent by Indian press.